2003
DOI: 10.1002/app.12418
|View full text |Cite
|
Sign up to set email alerts
|

Structure and gas separation properties of composite films based on polyaniline

Abstract: ABSTRACT:Composite films based on the polyvinyltrimethylsilane (PVTMS) with polyaniline (PANI) coating were obtained by borderline polymerization of aniline. The obtained coating was shown to differ from the polymer forming in the reaction mixture bulk both in chemical structure and morphology. Ratio and concentration of the reagents, mixing rate, reaction time, and condition of support surface were among the investigated factors affecting the growth and quality of PANI coating. The gas separation characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…If all the monomer has not been consumed in the formation of a colloid, then the subsequent start of precipitation polymerization begins to produce a precipitate along with the particles. It has indeed been observed that, if the monomer had been consumed in the surface polymerization on a suitable substrate, no polymer precipitate was produced in the aqueous phase [9,13,17,25]. Similarly, if all the monomer had been converted to produce colloidal particles by the polymerization at the stabilizer, there would be no contaminating precipitate.…”
Section: Colloidal Particles Together With a Precipitatementioning
confidence: 92%
See 1 more Smart Citation
“…If all the monomer has not been consumed in the formation of a colloid, then the subsequent start of precipitation polymerization begins to produce a precipitate along with the particles. It has indeed been observed that, if the monomer had been consumed in the surface polymerization on a suitable substrate, no polymer precipitate was produced in the aqueous phase [9,13,17,25]. Similarly, if all the monomer had been converted to produce colloidal particles by the polymerization at the stabilizer, there would be no contaminating precipitate.…”
Section: Colloidal Particles Together With a Precipitatementioning
confidence: 92%
“…Conducting polymer films can also be grown on various surfaces provided by microparticles [16,17], microspheres [18][19][20][21], or larger particles such as wood sawdust [22] and ferrites [23], membranes [24,25], porous and layered materials [26,27], and fibers [9,[28][29][30][31][32]. It has been observed that the introduction of various substrates with a large specific surface area into the reaction mixture accelerates the polymerization of aniline.…”
Section: Introductionmentioning
confidence: 99%
“…PANI films have been grown on the flat surfaces of glass [16][17][18][19][20], silicon [26,27], various polymers [28,29], and noble metals [30][31][32]. Many other template morphologies have also been tested: carbon nanotubes [33], polymer fibers and textiles [21,34,35], membranes [36,37], polymer microspheres [38,39], natural particulate materials, like wood sawdust [19], and others have been coated with PANI.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention has been paid to montmorillonite and related clays [45][46][47][48]. The applications of surface-modified substrates range from sensors and electronic noses [18,49], electrodes [30,50], conducting fillers [51], electro-rheological suspensions [42,48,52], corrosion protection [45], gas-separation membranes [29], and catalysis of organic reactions [53] to electromagnetic interference shielding [34] or increasing the dielectric breakdown of polymer films [28].…”
Section: Introductionmentioning
confidence: 99%
“…One of its interesting features is that, in addition to a bulk precipitate, it forms a thin film on the surface of the material (e.g. glass [4], another polymer [5,6], carbon nanotubes [7], silicon [8,9], noble metals [9][10][11], or even wood [12]) in direct contact with the polymerization mixture. Consequently, it has been thoroughly investigated as a surface modifier for multiple applications, such as flexible electrodes, conductive fibers, organic field transistors, electrochromic glasses, anticorrosive coatings, biosensors, gas separation membranes, or catalysts [6,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%